A retrospective study on epidemiology and outcomes of peripartum hysterectomy - Gupta, Kamna; Maurya, Aditi; Bhandari, Aditi; Jorwal, Anju (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Peripartum hysterectomy is a rare condition which is associated with maternal morbidity and mortality, and the last resort to control hemorrhage when all the other methods fail. The main aim of this study was to evaluate the indications, incidence and complications, maternal and perinatal outcome and compare the risk of peripartum hysterectomy in women who underwent LSCS previously with the women who did not have previous LSCS. Methods: A retrospective study was done over one year at a tertiary care teaching hospital in southern Rajasthan. All the women who underwent peripartum hysterectomy were included. Patients were divided into two groups, one who did not have any previous lower segment caesarean section (LSCS) and other who had history of previous LSCS, and their data was compared. The, results were calculated and represented as mean, frequency or median as appropriate. Results: 34 women underwent peripartum hysterectomy yielding the incidence of 2.21/ 1000 deliveries. The main indication of peripartum hysterectomy was abnormally adherent placenta followed by rupture uterus. 73% cases of peripartum hysterectomy were associated was the history of LSCS. Conclusions: The indication of peripartum hysterectomy has changed from atonic PPH to placenta spectrum syndrome. A major change can be brought about by the reduction of index cases of LSCS which has been on the rise in the recent years. Strict protocols should be made. Early transportation facility and institutional deliveries should be promoted to prevent the emergency peripartum hysterectomy.